2021
DOI: 10.3390/nu14010023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet Quality in Mediating the Association between Ultra-Processed Food Intake, Obesity and Health-Related Outcomes: A Review of Prospective Cohort Studies

Abstract: Prospective cohort studies show that higher intakes of ultra-processed food (UPF) increase the risk of obesity and obesity-related outcomes, including cardiovascular disease, cancer and type 2 diabetes. Whether ultra-processing itself is detrimental, or whether UPFs just have a lower nutritional quality, is debated. Higher UPF intakes are inversely associated with fruit, vegetables, legumes and seafood consumption. Therefore, the association between UPFs and poor health could simply be from excess nutrient int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 154 publications
(358 reference statements)
0
86
0
4
Order By: Relevance
“…The high rates of excess negative nutrients across these diverse NPMs are likely related to the high proportion of UPFs. Studies have shown that UPFs are associated with overweight and obesity, type 2 diabetes, depression, cardiovascular and cerebrovascular disease, and mortality [6,7,44]. The negative impact on health may be associated with the poor nutritional quality of UPFs.…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of excess negative nutrients across these diverse NPMs are likely related to the high proportion of UPFs. Studies have shown that UPFs are associated with overweight and obesity, type 2 diabetes, depression, cardiovascular and cerebrovascular disease, and mortality [6,7,44]. The negative impact on health may be associated with the poor nutritional quality of UPFs.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is noteworthy that the association between UPF and VAT in our population remained after adjustment for both dietary factors and BMI. Whether the associations between UPF and health outcomes are mediated by overall diet quality or not is actively debated, but overall, the associations appear to be robust when adjusting for both nutrients (e.g., saturated fat, sugars, sodium) and dietary patterns (e.g., Mediterranean diet) ( 32 ). The underlying mechanisms driving this association is unclear and warrants further investigation ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Monteiro and colleagues [11] established a system known as "NOVA". Since then, it has become the most widely used system in the research field [2,6,12].…”
Section: An Overview Of Ultra-processed Foodsmentioning
confidence: 99%